1550 nm excitation-responsive upconversion nanoparticles to establish dual-photodynamic therapy against pancreatic tumors. Issue 3 (23rd December 2020) - Pham, Khang-Yen; Wang, Liu-Chun; Hsieh, Chia-Ching; Hsu, Ya-Ping; Chang, Li-Chan; Su, Wen-Pin; Chien, Yi-Hsin; Yeh, Chen-Sheng
Abstract : The marriage between 1550 nm (NIR-IIb) light excitation and dual-photodynamic therapy for upconversion UCNP@SiO2 /RB, Ce6-PEG nanoparticles to generate 1 O2 showing a synergetic effect against pancreatic tumors in vitro and in vivo . Abstract : The second near-infrared biological window b (NIR-IIb, 1500–1700 nm) is recently considered as the promising region for deeper tissue penetration. Herein, a nanocarrier for 1550 nm light-responsive dual-photodynamic therapy (PDT) is developed to efficiently boost singlet oxygen ( 1 O2 ) generation. The dual-photosensitizers (PSs), rose bengal (RB) and chlorin e6 (Ce6), are carried by the silica-coated core–shell LiYbF4 :Er@LiGdF4 upconversion nanoparticles (UCNPs), forming UCNP/RB, Ce6. Following 1550 nm laser irradiation, the upconversion emission of UCNP/RB, Ce6 in both green (∼550 nm) and red (∼670 nm) colors is fully utilized to activate RB and Ce6, respectively. The simultaneous triggering of dual-PS generates an abundant amount of 1 O2 resulting in boosted PDT efficacy. This dual-PDT nanocarrier presents an enhanced anticancer effect under single dose treatment in comparison with the single-PS ones from in vitro and in vivo treatments. The marriage between the boosted dual-PDT and 1550 nm light excitation is anticipated to provide a new avenue for non-invasive therapy.